SPATIO-TEMPORAL DISTRIBUTION OF EVAPOTRANSPIRATION IN NORTHWESTERN SÃO PAULO STATE, BRAZIL - De Oliveira, Daniela Araújo [UNESP]; Hernandez, Fernando Braz Tangerino [UNESP]; De Carvalho Bispo, Regiane; De Castro Teixeira, Antonio Heriberto (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
The remote sensing became an important tool in agriculture, mainly in obtaining data on weather variables, like the range of evapotranspiration averages. This way, this work aimed to estimate the evapotranspiration in a regional scale in the Paulista Northwest and it’s temporal and spatial distribution by using SAFER (Simple Algorithm for Evapotranspiration Retrieving) algorithm and images from the satellites Landsat 5 and Landsat 8 in 2010, 2017, and 2018. The SAFER algorithm showed effective for estimating evapotranspiration in large scale and this methodology can be applied in further studies to monitor agricultural and climatological indicators of the region. The medium values of evapotranspiration ranged from 0.5 and 2.5 mm day-1, being the highest values were recorded in the irrigated areas. Regionally, the highest averages were obtained in the rainy season of the region, with values close to 2 mm day-1.
DISTRIBUIÇÃO ESPAÇO-TEMPORAL DA EVAPOTRANSPIRAÇÃO NO NOROESTE PAULISTA
Keywords: large scale; remote sensing; SAFER